SISTEM KEAMANAN HELM BERBASIS IOT DENGAN LAYANAN AKSES LOKASI MENGGUNAKAN TELEGRAM - Wandari, Fitri; Meisya Suandari; Irwan; Ocsirendi (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Helmet theft is a common problem for motorcycle users, especially on campuses. An Internet of Things (IoT) security system with location access via Telegram is designed to enhance helmet security. This system uses the HC-05 Bluetooth module as a master on the motorcycle and a slave on the helmet. If the connection is lost, a buzzer will sound and the ESP8266 module will send a notification to Telegram. The SIM900A module receives user commands, allowing them to send a